Kajian Aktivitas Antioksidan Dari Kayu Secang (Caesalpinia Sappan L.) - Kuncoro Hadi; Cindy Setiami; Wanda Azizah; Widya Hidayah; Yuni Fatisa (Sistem Informasi, 2023)
Free radicals can weaken the function of cell membranes and endoplasmic reticulum and destroy cells at the DNA molecular level. The human body needs antioxidants to stabilize the number of free radicals in the body. Natural antioxidants found in plants include vitamins, phenols, flavonoids, and carotenoids. Sappan wood is a herbal plant that has antioxidant properties. The antioxidant compounds contained in sappan wood are phenolic compounds, resorcinins, brazilein, gallic acid, flavonoids, saponins, terpenoids, and tannins. The method used is a literature study which is reviewed one by one, after which the journals obtained are collected and the information is compiled by summarizing the contents of the journals used as sources. From the processed data, sappan wood has an antioxidant activity which can be seen from the In Vitro test with the IC50 value and the In Vivo test on rats. Sappan wood is used as a cosmetic ingredient in the form of essence and hair tonic. Apart from that, it is also used as an ingredient in the manufacture of drinks and food because sappan wood has high antioxidants.